5α-reductase activity in women with polycystic ovary syndrome: a systematic review and meta-analysis - Chuyan Wu; Ke Wei; Zhongli Jiang (BMC, 2017)
Abstract Background 5α-reductase activity might be important during the development of polycystic ovary syndrome (PCOS). However, the changes of 5α-reductase activity in PCOS subjects and the relationship between 5α-reductase activity and body mass index (BMI), insulin resistance (IR) remain largely unknown. Methods We performed a meta-analysis to examine 5α-reductase activity in women with PCOS; exploratory subgroup analyses were also performed. Results Five articles (with 356 cases and 236 controls) reporting 5α-reductase activity in patients with PCOS were selected for the meta-analysis. We observed significantly higher ratios of 5αTHF/THF (5α-reduced tetrahydrocortisol to 5β-reduced tetrahydrocortisol) and An/Et (androsteroneto/etiocholanolone) levels, which were used to assess 5α-reductase activity, among the patients with PCOS, [standardized mean differences (SMD) =0.43, 95%confidence intervals (95%CI) =0.25-0.61, P < 0.00001; SMD = 0.86, 95% CI = 0.29-1.44, P = 0.003]. We observed significant heterogeneity between studies for An/Et (I2 = 89% and P < 0.00001). According to the group analysis, women with PCOS exhibited increased 5α-reductase activity which was significantly associated with homeostasis model assessment of insulin resistance (HOMA-IR) regardless of obesity. Conclusions 5α-reductase activity was enhanced in women with PCOS. Increased 5α-reductase activity in patients with PCOS was related to IR.